Meta-analysis on Research about Political Communication on Social Media in Spain and Latin America - Mancera Rueda, Ana (Círculo de Lingüística Aplicada a la Comunicación, 2025)
The purpose of this article is to create the most accurate map possible of scientific research from the last decade regarding political communication on social media in Spain and Latin America. To achieve this, we will conduct a meta-analysis based on a sample of 515 academic works in this field, published between 2014 and 2024, which have been gathered from the Web of Science, Scopus, and Dialnet databases. With this, we aim to contribute to the discussion about the challenges and opportunities that the digital ecosystem presents for communication between politicians or government institutions and citizens.
Keywords: digital communication; social media; political marketing; methodology